2019
DOI: 10.1111/tbj.13238
|View full text |Cite
|
Sign up to set email alerts
|

Papillary and sclerosing lesions of the breast detected and biopsied by MRI: Clinical management, upgrade rate, and association with apocrine metaplasia

Abstract: Benign papillary and sclerosing lesions of the breast (intraductal papillomas, complex sclerosing lesions, radial scars) are considered high-risk lesions due to the potential for upgrade to carcinoma on subsequent surgical excision. Optimal clinical management of such lesions remains unclear due to variable reported upgrade rates. Apocrine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Heller et al documented an upgrade rate of 8% for papillary lesions. These results may suggest that recent guideline recommendations might also apply on high-risk patients with papillary and sclerosing lesions detected and biopsied by MRI-VAB [75,76]. Histologic diagnosis of papillary lesions is still challenging.…”
Section: Future Perspectivementioning
confidence: 96%
“…Heller et al documented an upgrade rate of 8% for papillary lesions. These results may suggest that recent guideline recommendations might also apply on high-risk patients with papillary and sclerosing lesions detected and biopsied by MRI-VAB [75,76]. Histologic diagnosis of papillary lesions is still challenging.…”
Section: Future Perspectivementioning
confidence: 96%
“…A prior detailed subanalysis of these lesions found that complex sclerosing lesions were more likely to have washout kinetics and intraductal papillomas to have a larger proportion of cases with T2 hyperintense features. 12 In this study, we were unable to identify discriminating imaging characteristics of papillary and sclerosing lesions that reliably allow for differentiation from malignant entities. The clinical significance of increased detection of such papillary and sclerosing lesions, which are often considered “high-risk,” remains uncertain with differing outcomes and recommendations.…”
Section: Discussionmentioning
confidence: 82%
“…Prior reports describe the clinical management (and upgrade rates) of these lesions from portions of this patient cohort. 12 , 19 …”
Section: Discussionmentioning
confidence: 99%